Psychology, pedagogy, and assessment in serious games - Connolly, Thomas M. (Hershey, Pennsylvania : Information Science Reference, 2014)
'This book addresses issues the potential of games to support learning and change behaviour offering empirical evidence pertaining to the effectiveness of Serious Games in the key areas of psychology, pedagogy, and assessment'--
'Premier Reference Source'--Cover.
Includes bibliographical references (pages 420-480) and index.
Keywords: Video games -- Psychological aspects; Computer games -- Psychological aspects